Age at diagnosis predicts deterioration in glycaemic control among children and adolescents with type 1 diabetes. Issue 1 (7th October 2014) - Clements, Mark A; Lind, Marcus; Raman, Sripriya; Patton, Susana R; Lipska, Kasia J; Fridlington, Amanda G; Tang, Fengming; Jones, Phil G; Wu, Yue; Spertus, John A; Kosiborod, Mikhail
Abstract : Background: Poor glycemic control early in the course of type 1 diabetes mellitus (T1DM) increases the risk for microvascular complications. However, predictors of deteriorating control after diagnosis have not been described, making it difficult to identify high-risk patients and proactively provide aggressive interventions. Objective: We examined whether diagnostic age, gender, and race were associated with deteriorating glycemic control during the first 5 years after diagnosis. Participants: 2218 pediatric patients with T1DM. Methods: We conducted a longitudinal cohort study of pediatric patients with T1DM from the Midwest USA, 1993–2009, evaluating within-patient glycated hemoglobin (HbA1c) trajectories constructed from all available HbA1c values within 5 years of diagnosis. Results: 52.6% of patients were male; 86.1% were non-Hispanic Caucasian. The mean diagnostic age was 9.0±4.1 years. The mean number of HbA1c values/year/participant was 2.4±0.9. HbA1c trajectories differed markedly across age groups, with older patients experiencing greater deterioration than their younger counterparts (p<0.001). HbA1c trajectories, stratified by age, varied markedly by race (p for race×diagnostic age <0.001). Non-Hispanic African-American patients experienced higher initial HbA1c (8.7% vs 7.6% (71.6 vs 59.6 mmol/mol); p<0.001), and greater deterioration in HbA1c than non-Hispanic Caucasian patients across diagnostic ages (rise of 2.04% vs 0.99% per year (22.3 vs 10.8 mmol/mol/year); p<0.0001). Conclusions: Older diagnostic age and black race are major risk factors for deterioration in glycemic control early in the course of T1DM. These findings can inform efforts to explore the reasons behind these differences and develop preventive interventions for high-risk patients.